ITGBL1 transcriptionally inhibited by JDP2 promotes the development of pancreatic cancer through the TGF-beta/Smad pathway - Du,Tiancong (2022)
Pancreatic cancer (PC) is one of the malignant tumors with the worst prognosis worldwide because of a lack of early diagnostic markers and efficient therapies. Integrin, beta-like 1 (ITGBL1) is a β-integrin-related extracellular matrix protein and is reported to promote progression of some types of cancer. Nevertheless, the function of ITGBL1 in PC is still not clear. Herein, we found that ITGBL1 was highly expressed in PC tissues compared to normal tissues (P<0.05) and PC patients with higher TGBL1 expression showed worse prognosis. PANC-1 and AsPC-1 cells were used for gain/loss-of-function experiments. We found that ITGBL1-silenced cells exhibited decreased proliferation, migration, and invasion abilities and delayed cell cycle, whereas ITGBL1 overexpression reversed these malignant behaviors. ITGBL1 was also demonstrated to activate the TGF-β/Smad pathway, a key signaling pathway in PC progression. Additionally, ITGBL1 expression was found to be suppressed by a suppressor of PC progression, c-Jun dimerization protein 2 (JDP2). Results of dual-luciferase assay indicated that transcription factor JDP2 could inhibit TGBL1 promoter activity. ITGBL1 overexpression inversed the effects of JDP2 up-regulation on cell function. Collectively, we concluded that ITGBL1 may be transcriptionally suppressed by JDP2 and promote PC progression through the TGF-β/Smad pathway, indicating that ITGBL1 may have therapeutic potential for the treatment of PC.